Metrics to analyze and improve diets through food systems in low and middle income countries - Melesse, Mequanint B.; Berg, Marrit van den; Béné, Christophe; de Brauw, Alan; Brouwer, Inge D. (Springer, 2020)
Taking a food systems approach is a promising strategy for improving diets. Implementing such an approach would require the use of a comprehensive set of metrics to characterize food systems, set meaningful goals, track food system performance, and evaluate the impacts of food system interventions. Food system metrics are also useful to structure debates and communicate to policy makers and the general public. This paper provides an updated analytical framework of food systems and uses this to identify systematically relevant metrics and indicators based on data availability in low and middle income countries. We conclude that public data are relatively well available for food system drivers and outcomes, but not for all of the food system activities. With only minor additional investments, existing surveys could be extended to cover a large part of the required additional data. For some indicators, however, targeted data collection efforts are needed. As the list of indicators partly overlaps with the indicators for the Sustainable Development Goals (SGDs), part of the collected data could serve not only to describe and monitor food systems, but also to track progress towards attaining the SDGs.